Factors Affecting Adult Captures of the Cotton Bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) in Pheromone-Baited Traps - Alkiviadis Karakasis; Evagelia Lampiri; Christos I. Rumbos; Christos G. Athanassiou (Agronomy, 2021)
The effects of funnel-trap color, trap height and pheromone formulation on the adult captures of the cotton bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) were evaluated in traps that were suspended in cotton fields in central Greece. Briefly, in a first trial, the efficacy of funnel traps of three different colors, i.e., green, striped (with black and white stripes) and white, was comparatively evaluated, whereas in a second trial green funnel traps were placed at three heights, i.e., 30, 60 and 90 cm from the ground. Finally, in a third trial we tested the efficiency of green funnel traps with three commercially available pheromone lures. Considering the overall captures, trap color and pheromone formulation affected male captures, whereas trap height had no influence. Captures notably increased in all traps from late August to mid-September. In total, the white funnel trap captured more moths than the green or striped funnel traps. Placement of the traps at different heights did not significantly affect captures, but seasonal differences were observed at individual dates during the trapping period. Barrettine’s pheromone lure provided significantly more captures than the other two (Russell, Trécé) in some of the trap-check dates. The results can be further utilized in the monitoring protocols of H. armigera in cotton fields.